The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1016/j.ejcts.2007.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of prolonged mechanical ventilation following aorta no-touch off-pump coronary artery bypass surgery

Abstract: In this study, PMV following aorta no-touch OPCAB was related to preoperative variables: age, octogenarians, preoperative IABP, TIA, and stroke. There was no relation between PMV and any of the operative data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
14
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 18 publications
5
14
0
Order By: Relevance
“…6,7 A number of studies regarding PMV following cardiac surgery have examined its predictors or its influence on clinical outcomes and costs. [8][9][10][11][12][13][14][15][16][17] However, little is known about PMV following AAAD surgery. The aim of this retrospective study was to identify predictors of PMV following AAAD surgery and to assess the influence of PMV on the short and long-term postoperative courses.…”
mentioning
confidence: 99%
“…6,7 A number of studies regarding PMV following cardiac surgery have examined its predictors or its influence on clinical outcomes and costs. [8][9][10][11][12][13][14][15][16][17] However, little is known about PMV following AAAD surgery. The aim of this retrospective study was to identify predictors of PMV following AAAD surgery and to assess the influence of PMV on the short and long-term postoperative courses.…”
mentioning
confidence: 99%
“…[12][13][14] Due to a system of risk factors (such as the duration of surgery, anesthesia, clinical condition, mode of ventilator therapy, and method of weaning from mechanical ventilation), many patients should receive prolonged mechanical ventilation. [15][16][17] It was reported that the prolonged mechanical ventilation could prolong the hospital and intensive care unit (ICU) stay, 18) increase the burden of patients, and raise the risk of cerebral palsy, postoperative atrial fibrillation or ventilator-associated pneumonia.19-21) Thus, it is necessary to reduce the duration of mechanical ventilation in patients requiring prolonged mechanical ventilation.A previous study has showed that early rehabilitation therapy in ICU after CABG could significantly improve the outcomes of patients with less than 72 hours of mechanical ventilation.22) However, it is still unknown whether early rehabilitation therapy could improve the clinical outcomes and reduce the duration of mechanical ventilation in patients requiring over 72 hours of mechanical ventilation after CABG. Thus, we performed this study to evaluate the influence of early rehaFrom the…”
mentioning
confidence: 99%
“…[12][13][14] Due to a system of risk factors (such as the duration of surgery, anesthesia, clinical condition, mode of ventilator therapy, and method of weaning from mechanical ventilation), many patients should receive prolonged mechanical ventilation. [15][16][17] It was reported that the prolonged mechanical ventilation could prolong the hospital and intensive care unit (ICU) stay, 18) increase the burden of patients, and raise the risk of cerebral palsy, postoperative atrial fibrillation or ventilator-associated pneumonia. [19][20][21] Thus, it is necessary to reduce the duration of mechanical ventilation in patients requiring prolonged mechanical ventilation.…”
mentioning
confidence: 99%
“…Some studies, on the other hand have found older age as a risk factor of delayed extubation and these studies have found age >65 year is a risk factor of delayed extubation after surgery. 11,12 According to Suematsu et al risk of delayed extubation is increased in patients with age >70 Years. 3 In our study, there was no effect of female gender on delayed extubation.…”
Section: Discussionmentioning
confidence: 99%
“…22 Dunning et al 23 found that left ventricular systolic dysfunction and urgency of the procedure as independent risk factors of prolonged ventilation after surgery. Prapas et al 11 concluded that periop need IABP insertion is also an independent risk factor of delayed extubation after CABG surgery. According to Shirzadet al 24 atrial fibrillation, sudden cardiac arrest and need for intubation are common risk factors of delayed extubation after valvular heart surgery.…”
Section: Early Extubation (N=55) Delayed Extubation (N=26) P-valuementioning
confidence: 99%